PERBANDINGAN BOBOT TUBUH DAN KARKAS BANDIKUT JANTAN DAN BETINA DEWASA - Dirwan Muchlis (AGRICOLA, 2011)
The purpose of research is the comparison between body and percentage of charkas also percentage others parts like charkas bandicoot child and adult. The result of this research we hope that can be use as the first information and try to take care for animal and future. This research need one month to finished start from February,19-2007 until march 19-2007 in Kelapa Lima District - Merauke.Observed the variable is ability of body, percentage charkas and percentage parts of charkas (% high, % breast, % back bone,% back high) . Data should be analysis use descriptive statistic method. Compare with ability of body, percentage charkas and part of charkas by use experiment for level of believing 95%The result of this research shows rate by body ability from bandicoot. The results of experiment body ability and parts of bandicoot (% high, % breast,% back bone and back high) the fact that bandicoot show different